Structure of natural Juniperus excelsa stands in Northwest of Iran - FARZAM TAVANKAR (Society for Indonesian Biodiversity, 2015)
Tavankar F. 2015.Structure of natural Juniperus excelsa stands in Northwest of Iran. Biodiversitas 16: 161-167. Juniperusexcelsa M. Bieb. stands are important forest ecosystems in mountain areas of Iran. In this research the structure of J. excelsa stands wasstudied at altitudes of 1,400 to 1,900 m in northwest of Iran. The results showed that the mean densities of trees and seedling (trees withheight up to 1.3 m) were 99.8 ± 32.0 and 70.5 ± 18.3 stem ha-1, respectively. The juniper trees comprise 52.8% of the total tree density,while the juniper seedlings comprise 19.3% of total seedling density. The mean of basal area in this stand was 3.12 ± 0.3 m2 ha-1 and themean of canopy cover was 42.7 ± 17.9 percent. The mean of trees height was obtained 2.75 ± 1.1 m. The total of 28 woody speciesbelonging to 14 families was recorded from the study area. The juniper trees had the maximum value of species importance value(SIV=87.3). Amygdalus lyciodes and Pistacia atlantica were two tree species that have high SIV values, 34.1 and 27.0, respectively.Thedistribution of trees density in different tree diameters resemble to a reverse J-shaped indicating uneven-aged structure. The resultsindicated juniper seedlings were increased by increasing stand crown cover (P< 0.01). Moreover extreme environmental conditions,grazing and timber harvesting for firewood are two important socioeconomic problems in these forests. These valuable stands needs tourgently conservation strategies.